Beyond the shadows - Weeks, Brent (New York : Orbit, 2008)
In the trilogy's conclusion, Kylar Stern is hired for one last job--to assassinate a goddess.
Includes excerpt from: Orcs (p. [695]-708).
Keywords: Assassins -- Fiction; Fantasy fiction; Fiction